Structural studies and influence of the structure on the electrical and optical properties of microcrystalline silicon thin films produced by RF sputtering - Cerqueira, M. F. (2000)
Microcrystalline silicon thin films were produced by reactive magnetron sputtering on glass substrates under several different conditions (RF power and gas mixture composition). The film structure was studied by X-ray diffractometry (XRD), transmission electron microscopy (TEM) and Raman spectroscopy, allowing the determination of crystal sizes, crystallinity and mechanical strain. These parameters were evaluated by fitting a pseudo-Voigt function to the X-ray data, and by the application of the strong phonon confinement model to the Raman spectra. The degree of crystallinity and the presence of single crystals or crystal agglomerates, which was confirmed by TEM, depends on the preparation conditions, and strongly affects the optical spectra and the electrical transport properties.